Consumindo celebridades: visibilidade midiática e afirmação de si na blogosfera - Pessoa, Camille Silva Sales (2009)
A celebrity factory supplies the stars market, and almost at the same time it let them in a condition of ostracism. Following the speed of the contemporary experiences, to understand the phenomenon of the exposure on media, this work has two parts star system and pós star system . The privacy of star s lives once so protected, is suddenly exposed to anyone, therefore we are facing a new era of star´s visibility. Thinking of that the questions is: Which are the impacts of this new star s world on the mass media, especially blogs? Which are the particularitities of the media exposure trough blogs? How these shared on-line diaries affects the construction of image and subjective production? Investigating the ways of appropriation ,the blog of the model and actress Luana Piovani was chosen in order to analyze its role in communication specially trough it s visual resources and narrative associated with the effort to guarantee a place as an authentic and dynamic producer of media´s celebrities